Changes in Inequality of Educational Opportunity The Long-Term Development in Germany - Blossfeld, Pia Nicoletta (Springer Fachmedien Wiesbaden : VS, 2018)
Pia Nicoletta Blossfeld provides a long-term longitudinal analysis of the stepwise changes in transitions over the educational careers in East and West Germany using data from the National Educational Panel Study (NEPS). She examines how far reforms aimed to increase the permeability in the German educational system have changed the movements of children, adolescents and young adults in Germany since the last four decades. Her book contributes to the literature of educational sociology by studying the associations between various resources of family background and respondent's educational histories until final educational attainment. A novelty of her book is the analysis of the role of intercohort changes in social background composition on final educational attainment. Contents The Educational Systems in East and West Germany Expansion of the Transition to Upper Secondary School and Its Consequences Mobility Flows between Vocational and Academic Tracks Intercohort Compositional Change of Social Origin Target Groups Researchers and students in the fields of sociology, educational research, education, pedagogy, political science, and economics Practitioners, administrators, and policy makers in the educational field The Author Dr. Pia N. Blossfeld is a postdoctoral researcher at the University of Leipzig, Germany. .